2022
DOI: 10.1111/cas.15268
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from M1‐polarized macrophages promote apoptosis in lung adenocarcinoma via the miR‐181a‐5p/ETS1/STK16 axis

Abstract: Serine/threonine kinase 16 (STK16) is crucial in on regulating tumor cell proliferation, apoptosis, and prognosis. Activated M1 macrophages regulate lung adenocarcinoma (LUAD) growth by releasing exosomes. This study aims to investigate the role of STK16 and then focus on the possible mechanisms through which exosomes derived from M1 macrophages play their roles in LUAD cells by targeting STK16. Clinical LUAD samples were used to evaluate the expression of STK16 and its association with prognosis. Exosomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…15 Consistently, the results of the present study showed Interestingly, it was also reported that cancer-associated fibroblast, another major cell in TME, delivered exosomal miR-181a-5p to a lung cancer cell to promote cell apoptosis. 13 From these results, it could be inferred that miR-181a-5p play as a critical regulator in the cross talk of tumor cells and TME.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…15 Consistently, the results of the present study showed Interestingly, it was also reported that cancer-associated fibroblast, another major cell in TME, delivered exosomal miR-181a-5p to a lung cancer cell to promote cell apoptosis. 13 From these results, it could be inferred that miR-181a-5p play as a critical regulator in the cross talk of tumor cells and TME.…”
Section: Discussionmentioning
confidence: 93%
“…It was demonstrated that miR-181a-5p acted as an oncogene in multiple cancers. 13,26 For instance, miR-181a-5p was known to be upregulated in osteosarcoma and play as a tumorpromoting role via accelerating cell proliferation and decreasing cell apoptosis. 15 Consistently, the results of the present study showed Interestingly, it was also reported that cancer-associated fibroblast, another major cell in TME, delivered exosomal miR-181a-5p to a lung cancer cell to promote cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 72 M1-Exos can carry miR-181a-5p to target ETS1 to inhibit the expression of STK16 in tumor cells, thereby reducing cell viability and promoting apoptosis of lung adenocarcinoma cells. 73 In addition, M1-Exos can also carry miR-16-5p to reduce the expression of PD-L1 in gastric cancer cells, thus reducing the inhibitory effect of immune checkpoints on T cells and promoting the activation and killing ability of T cells. 74 Chiara cianciaruso et al collected EVs released from TAM (TAM-EV) of mice and performed quantitative, proteomic, and lipidomic analyses of them.…”
Section: The Role Of Exosomes From Different Immune Cell Sources In T...mentioning
confidence: 99%
“…Serine/threonine kinase 16 (STK16), a membrane-associated kinase, is involved in the regulation of cell proliferation, apoptosis, sEV signaling pathways, and metabolism ( Wang et al, 2019b ). MiRNA-181a-5p delivered by M1-sEVs inhibit the expression of STK16 by targeting ETS1 to regulate cell viability and apoptosis in lung adenocarcinoma (LUAD), while STK16 silencing significantly reduces the mass of nodules in tumor models, thus promoting the apoptosis of LUAD cells ( Wang et al, 2022a ). Serum miRNA-181a-5p was considered a potential noninvasive biomarker for the diagnosis and prognosis of patients with non-small cell lung cancer (NSCLC), while a further argument may be needed.…”
Section: Role Of M-sevs In Cancermentioning
confidence: 99%